Psychiatric morbidity and cognitive ability in children with β-thalassemia: A hospital-based cross-sectional study - P. C. Pradeep Kumar; J. Shivananda Manohar; Anu Janardhan; Rajesh Raman (Archives of Mental Health)
Background: β-Thalassemia, a major blood disease in children, has been found to have significant mental health implications. This study aims to assess differences in psychiatric comorbidities, coping strategies, and nonverbal intelligence/cognitive abilities among male and female children with blood transfusion-dependent thalassemia (β-thalassemia). Materials and Methods: This cross-sectional study involved 45 children diagnosed with β-thalassemia who regularly visit the hospital for blood transfusion. These children were recruited through purposive sampling. A socio-demographic data sheet, Revised Child Anxiety and Depression Scale, Children Coping Strategies Checklist Revision 1, and Raven’s Colored Progressive Matrices (R-CPM) were used to measure anxiety, depression, other comorbidities, coping, and nonverbal/cognitive abilities in children. Results: The sample included 26 males (mean age: 9.23 ± 1.39) and 19 females (mean age: 9.58 ± 1.50). Females exhibited higher mean scores in separation anxiety (Mean = 13.68 ± 4.79) and generalized anxiety (Mean = 8.26 ± 3.58), panic (Mean = 8.26 ± 3.58), and obsessive–compulsive disorder (Mean = 5.84 ± 6.17), while males scored higher in social phobia (Mean = 10 ± 3.42). Female children more frequently used problem-focused, support-seeking, and avoidant coping strategies. Both genders demonstrated high nonverbal intelligence, with most children scoring between 75 and 95 on the R-CPM. Conclusion: This study shows that psychiatric comorbidities in male and female children with β-thalassemia are almost similar. However, their nonverbal/cognitive are not affected.